1407. Increasing access to COVID-19 testing in underserved Black American neighborhoods. (15th December 2022) - Avery, Elizabeth; Olinger, Tamara; Suzuki, Sumihiro; Cartwright, Yolanda; Jenkins, LaDawne; Chaisson, Lelia H; Moss, Angela; Davis, Elizabeth; Logan, Latania K; Epting, Steve; Lynch, Elizabeth
Abstract: Background: Black Americans have been disproportionately impacted by COVID-19, with systemic inequities contributing to increased incidence and mortality. In Chicago, access to COVID-19 testing was scarce in many predominantly Black neighborhoods early in the pandemic, exacerbating inequities. We aimed to assess uptake and yield of a COVID-19 testing campaign to increase access in high-risk, underserved Chicago communities. Methods: The Alive Church Network (ACN) is a community-driven coalition of Black pastors and public health researchers developed to address health inequities in Chicago. For this initiative, ACN implemented two strategies to improve access to COVID-19 testing in underserved neighborhoods: 1) church-based testing, with nurses and community health workers (CHWs) stationed in churches to perform PCR testing for community members and church staff (Dec 2020-Dec 2021) and 2) community site testing, with nurses and CHWs deployed to 8 local sites (e.g., Salvation Army) to conduct weekly PCR testing for employees and clients (May 2021-Mar 2022). We assessed characteristics of individuals undergoing testing; symptom and exposure history; and COVID-19 positivity. In addition, we compared positivity for ACN sites with Chicago citywide positivity over time. Results: A total of 3420 tests were performed for 1703 individuals. Of those tested, 931 (54.7%) were tested at churches and 772 (45.3%) were tested at community partner sites. Those presenting to churches were older (mean 44.8 vs. 39.1 years), more likely to be female (56.5% vs. 48.5%), and more likely to have a chronic medical condition (37.1% vs. 22.5%, Table). Prevalence of COVID-19 symptoms and exposure history were similar for those presenting to church and community sites (Table). Overall, ACN test positivity was similar to Chicago citywide positivity; however, ACN test positivity was much higher during the Omicron surge (24% vs. 11%, Figure). Characteristics of individuals tested for COVID-19 at church and community sites COVID-19 test positivity, ACN sites vs. Chicago citywide Conclusion: The ACN testing campaign increased access to COVID-19 testing in underserved neighborhoods in Chicago and had high yield during the Omicron surge. Church-based testing was successful for reaching older, medically vulnerable individuals. Ensuring widespread access to testing is essential for health equity and to reduce COVID-19 morbidity and mortality. Disclosures: All Authors : No reported disclosures.